The impact of uric acid on musculoskeletal diseases: clinical associations and underlying mechanisms - Zhang, Jing; Sun, Na; Zhang, Wanhao; Yue, Wenjie; Qu, Xiaochen; Li, Zhonghai; Xu, Gang (Frontiers in Endocrinology, 2025)
Serum urate (SU) levels are significantly elevated in conditions such as gout, type 2 diabetes (T2D), obesity, and other metabolic syndromes. Recently, due to the high prevalence of hyperuricemia (HUA), numerous clinical connections between SU and musculoskeletal disorders like sarcopenia, osteoarthritis (OA), rheumatoid arthritis (RA), intervertebral disc degeneration (IDD), and osteoporosis (OP) have been identified. This review discusses the mechanisms linking SU to musculoskeletal disorders, as well as the clinical associations of SU with conditions such as sarcopenia, T2D with sarcopenia, McArdle disease, heart failure, gout, OA, IDD, OP and exercise-induced acute kidney injury (EIAKI), offering valuable insights for improved prevention and treatment strategies. Mechanisms linking SU to musculoskeletal disorders include oxidative stress, MSU (monosodium urate) crystal deposition, inflammation, and other factors. In adults, both age and SU levels should be considered for preventing sarcopenia, while gender and SU may directly impact muscle mass in children and adolescents. HUA and gout may be risk factors for OA progression, although some reports suggest otherwise. A U-shaped relationship between SU and IDD has been reported, particularly in Chinese men, indicating lower or higher SU level may be risk factors for IDD. Maintaining SU levels within a certain range may help prevent OP and fractures. Future research, including epidemiological studies and new pathogenesis findings, will further clarify the relationship between musculoskeletal diseases and SU.